Towards a methodology for the use of geo-information technology in disaster assessment - Dawie van Vuuren (Jàmbá, 2006)
Disaster assessment entails the description of disaster events and their impact on human lives, property and the environment. Information is a vital component of this process, and geo-information technology in particular should have a key role in this regard.